Predictors of in-hospital mortality in patients with non-variceal upper gastrointestinal bleeding - González González, José Alberto; Vázquez Elizondo, Genaro; García Compeán, Diego; Obed Gaytán Torres, Juan; Flores Rendón, Ángel Ricardo; Jáquez Quintana, Joel Omar; Garza Galindo, Aldo Azael; Cárdenas Sandoval, Martha Graciela; Maldonado Garza, Héctor Jesús (Sociedad Española de Patología Digestiva, 2011)
Objective: to determine the independent predictors of in-hospital death of Hispanic patients with nonvariceal upper gastrointestinal bleeding (NVUGB). Experimental design: prospective and observational trial. Patients: in a period between 2000 and 2009, all patients with NVUGB admitted to our hospital were studied. Demographical and clinical characteristics, endoscopic findings and laboratory tests were evaluated. χ² and Mann-Whitney U analyses were performed for comparisons, and binary logistic regression was employed to identify independent predictors of in-hospital mortality. Results: 1,067 patients were included, 65% male with a mean age of 58.8 years. Mean number of comorbidities per patient was 1.6 ± 0.76. The most frequent cause of bleeding were gastric and duodenal ulcers (55.4%); 278 patients (25.8%) received endoscopic treatment of which 69.1% had combined therapy. Rebleeding occurred in 36 patients (3.4%) of which 50% died. Inhospital mortality was 10.2%, of which only 3.1% was associated to bleeding. When comparing causes of death among patients with and without comorbidities, only hypovolemic shock was found significative (48.3 vs. 25%; p = 0.020). Binary logistic regression found that the number of comorbidities, Rockall scale serum albumin < 2.6 g/dL on admission; rebleeding and length of hospital stay were independent risk factors of in-hospital mortality. Conclusion: the number of comorbidities, the Rockall scale score, an albumin level < 2.6 g/dL, the presence of rebleeding and hospital stay were predictors of in-hospital mortality in patients with UNVGB.